Seismic Surface Wave as Supporting Method to Soil Investigation - Jusoh, H. (2022)
Soil borehole drilling with standard penetration test (SPT) is a conventional method for a subsurface profiling that able to determine soil bearing capacity. However, full investigation of high accuracy on the subsurface with additional boreholes is strenuous. This method is invasive and time consuming. The multichannel analysis surface wave (MASW) was used in this investigation to test the dependability of this method and potentially converting shear wave velocity, Vs, to SPT-N value. The dependability of the correlation between actual and calculated SPT-N value was high (R2 = 0.7256) by utilizing Vs values using the specified equation (Vs = 97N0.314). Throughout regression analysis, the SPT-N value can be determined based on the generated equation 0.0114Vs1.3721 in the form of power allometric. Hence, allowing the equation to be applied for the local region. A field study was conducted, and Vs profile revealed 80 m/s to 160 m/s of the upper layer at 2-3 m depth representing soft soil, followed by a 2 m layer of stiff soil with Vs in between 130 m/s and 170 m/s, then 4-10 m hard material with Vs in between 190 m/s to 280 m/s, before reaching a harder stratum of 350 m/s and more. As a result, the soil properties were determined and used for soil bearing capacity and factor of safety (FOS) of the slope calculation. Thus, MASW can be executed to determine SPT-N values providing supporting data to the conventional approach. Although, it is consider in the preliminary stage, the developed empirical equation in this study is intended to give a rapid preliminary approach and general view of the profile prior to site investigation/assessment for the geotechnical engineers. Â© 2022 American Institute of Physics Inc.. All rights reserved.